India: we can't rescue Europe. - Desai, Ashok V. (World Today)
The author compares economic police in India to economic policy in Europe. According to the article, companies in India have done well under a nationalized banking system that, combined with steady economic growth, has insulated the country from inflation. Topics include the printing of money, controlled economies, and economic conditions in Europe. The Indian Prime Minister Manmohan Singh is mentioned.